Gum Benzoin (Styrax benzoin) as Antibacterial against Staphylococcus aureus - Asih Gayatri; Eti Rohaeti; Irmanida Batubara (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
Gum benzoin (Styrax benzoin) is one of nontimber forest product classified into the resin group. The aim of the study was to determine the component from gum benzoin as an antibacterial against Staphylococcus aureus. Indonesian gum benzoin was obtained from North Sumatra and has antibacterial activity against S. aureus with the MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentrationo) values of its ethyl acetic extract of 1.00 mg/mL and 2.00 mg/mL, respectively. Thin layer chromatography (TLC) was used in purification of ethyl acetate extract of the gum benzoin. The active component was detected by TLC contact bioautography. The bands with Rf of 0.21, 0.77, and 0.87 had growth inhibition activity to the S. aureus. The active antibacterial band with Rf of 0.21 was isolated and it could be an alkaloid component.